Plant Diversity Assessment of Matarbari Area of Moheshkhali Upazila, Cox’s Bazar (Journal of Biodiversity Conservation and Bioresource Management, 2023)
The study presents the status of plant diversity in and around Matarbari, in Moheshkhali Upazila, Cox’s Bazar district, situated in the close vicinity of the Bay of Bengal. A total of 248 plant species belonging to 80 families was identified in the study area. For each plant species, the scientific name, local name, family, habit, habitat, origin, status, abundance, and uses are provided. The most dominant family is the Fabaceae, followed by Poaceae, Euphorbiaceae, Verbenaceae, Asteraceae, Convolvulaceae, Malvaceae, Mimosaceae, Moraceae, and Arecaceae. Most of the plant species are herbs, followed by trees, climbers, and shrubs. In the present study, the maximum numbers of plants recorded were from homesteads, followed by roadsides, mangroves, wetland, and sand dune habitats. The most important plant species were medicinal (28%), wildlifesupporting (20%), fruits and grains (10%), and so on. A few exotics (18%), including Eucalyptus camaldulensis, Albizia richardiana, Chromolaena odorata, Lantana camara, etc., some rare species (37 spp.), some mangrove plants, and 2 keystone species (Ficus altisimma and F. rumphii) were found in the study area that are of conservation concern. Besides, significant areas such as sand dunes, eco-parks, Jhao plantation area, and mangrove forests have been identified that should be of concern for any development and management projects in and around Matarbari. A number of threats, including infrastructural development activities, land filling, mangrove forest clearing for shrimp and salt cultivation, was also observed during field data collection. The concerned authorities, including the government, should consider the importance of natural plant diversity in implementing different mega projects.J. Biodivers. Conserv. Bioresour. Manag. 2022, 8(2): 89-102